Reduced pro-inflammatory profile of γδT cells in pregnant patients with rheumatoid arthritis. Issue 1 (December 2016) - Tham, Manuela; Schlör, Gabriele; Yerly, Daniel; Mueller, Christina; Surbek, Daniel; Villiger, Peter; Förger, Frauke
Abstract Background During pregnancy, many patients with rheumatoid arthritis (RA) experience disease improvement, whereas patients with ankylosing spondylitis often suffer from persistent active disease. Here we investigated whether pregnancy-related changes in disease activity were associated with changes in the proportion and function of γδT cells. Methods The study population comprised 55 patients with RA, 31 patients with ankylosing spondylitis, and 35 healthy controls. Among these participants, 28 RA patients, 21 ankylosing spondylitis patients, and 23 healthy controls were investigated once before conception when possible, at each trimester of pregnancy, and at 8 weeks postpartum. Data were compared with age-matched non-pregnant patients to obtain disease-related background. In all subjects, peripheral Vδ1 and Vδ2 T cells were analyzed for cell frequencies, the activation marker CD69, the cytotoxicity markers NKG2D and NKG2A, and the intracellular cytokines tumor necrosis factor (TNF)α, interferon (IFN)γ, interleukin (IL)-17 and IL-10. Results Pregnant patients showed a decreased Vδ2/Vδ1 ratio in the third trimester, which resulted from a slightly reduced proportion of Vδ2 cells. Changes in RA disease activity during pregnancy and postpartum were not associated with numerical proportions of γδT cells but with changes of the cell activation marker CD69 on Vδ1 and Vδ2 cells. Only RA patients showed reduced proportions of TNFα-positive Vδ1and Vδ2 cells and IFNγ-positive Vδ2 cells at the third trimester of pregnancy, a finding that was not apparent in the entire population of CD3 T cells. The proportions of IL-17-positive γδT cells and IL-10-positive γδT cells did not differ between pregnant and non-pregnant women of the different groups. Conclusions Changes of disease activity in pregnant RA patients were associated with functional changes in both γδT cell subsets. This reduced pro-inflammatory profile of γδT cells might contribute to the immunomodulation resulting in pregnancy-induced improvement of RA.